Factors affecting Corporate Capital Structure Decisions: An Empirical Examination of Multinational and Domestic UK companies. - Mattu, Jatinder (2010)
This paper contributes to corporate financial literature by examining the determinants of corporate capital structure in relation to UK multinational corporations (MNCs) and UK domestic companies (DCs). This is then broken down into industry level and comparisons are made. The results suggest that UK MNCs are attaining a higher leverage ratio compared to their UK counterparts. It also suggests that most reliable factor in explaining the capital structure in terms of leverage ratio for UK MNCs is Tangibility (-). UK DCs leverage ratio is reliably effected by profitability (-), size (-), growth (+) and non-debt tax shield (+). At industry level, the leverage ratio of firms in construction is reliably attributed to size (-) and growth (+), Oil and Gas firms are dependably influenced by profitability (-), size (-) and tangibility (-). The leverage ratios for the telecommunications industry are reliably explained by profitability (-), growth (+) and tangibility (-), firms in the tobacco with food and drink sector are dependably influenced by profitability (+), size (+) and non-debt tax shield (-). Empirical findings from this report appear to be varied compared to theoretical considerations and prior empirical evidence. Keywords: Capital structure, Leverage, UK MNCs, UK DCs, Profitability, Size, Growth, Tangibility, Non-debt tax shield.